(Im)prescribility of crimes against humanity in the Brazilian Federal Supreme court - de Brito , Ícaro Fellipe Alves Ferreira; Almeida, Maíra Gondim (Seven Editora, 2023)
The main purpose of this work is to analyze the standard of judgment of the Brazilian Federal Supreme Court (STF) regarding the imprescriptible nature of crimes against humanity. In this sense, the objective is to answer whether the STF interprets the incorporation of the imprescriptibility, provided in the Convention on the Non-applicability of War Crimes and Crimes against Humanity, in the Brazilian legal system. To this end, it uses a bibliographic and jurisprudential methodology to analyze the outlines of the Argumentation of Breach of Fundamental Precept (ADPF) 153, reported by Minister Eros Grau, as well as Extradition (Ext) 1362, reported by Minister Edson Fachin and conclude that the Supreme Court, although without unanimity, rejects the lack of a statute of limitations, arguing that in addition to Brazil not having subscribed to the above Convention, only domestic law can provide for the state's punitive claim. DOI: https://doi.org/10.56238/methofocusinterv1-018